Meningkatkan Hasil Belajar Dan Gotong Royong Siswa 12 IPS SMA Talenta Materi Keberagaman Melalui PBL Berbantuan Video - Petrus Stanislaus Siga (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2023)
This research was motivated by the low learning outcomes of class 12 IPS 1 students at SMA Talenta Bandung. The aim of this research is to determine the impact of implementing the video-assisted Problem Based Learning model on students' learning outcomes and mutual cooperation abilities. This type of research is Classroom Action Research (PTK). This research procedure uses C. Kemmis and Mc Taggart's spiral model, which consists of four stages, namely planning, implementation, observation and reflection. The subjects of this research were 21 grade 12 IPS 1 SMA Talenta Bandung students, consisting of 13 male students and 8 female students. Data collection techniques are carried out through observation and learning results tests. Data from observations and tests are then processed using descriptive analysis to describe the situation of increasing achievement of success indicators for each cycle for each variable. The results of the research show that the Problem Based Learning model assisted by video media is proven to be able to improve learning outcomes and mutual cooperation abilities of class 12 IPS 1 SMA Talenta Bandung students. This can be seen from the increase in student learning outcomes from the initial test to second cycle. In the initial test, only 3 students (14%) completed the test, while 18 students (86%) did not complete it. In the first cycle, 12 students had completed it (57%), while 9 students had not completed it (43%). In the second cycle, 19 students (90%) completed it, while 2 students (10%) did not complete it. In the ability of mutual cooperation, there has also been an improvement. In the first cycle, students' mutual cooperation ability was at 74% and in the second cycle, mutual cooperation ability reached 92%.